I'm a software architect, now what? leadership, relationships, and communication - Schutta, Nathaniel T. (O'Reilly Media, 2015)
"Becoming a software architect is a longed-for career upgrade for many software developers. While the job title suggests a work day focused on technical decision-making, the reality is quite different. In this video, software architect Nathaniel Schutta constructs a real world job description in which communication trumps coding."--Resource description page.
Title from title screen (viewed January 12, 2016). - Publisher and date from resource description page (Safari, viewed January 12, 2016)
Keywords: Software architecture; Architecture logicielle